Peer and Teacher-Selected Peer Buddies for Adolescents With Autism Spectrum Disorders: The Role of Social, Emotional, and Mentalizing Abilities. Issue 4 (18th May 2016) - Laghi, Fiorenzo; Federico, Francesca; Lonigro, Antonia; Levanto, Simona; Ferraro, Maurizio; Baumgartner, Emma; Baiocco, Roberto
ABSTRACT: This study examined mentalizing abilities, social behavior, and social impact of adolescents who expressed the willingness to become peer buddies for adolescents with Autism Spectrum Disorders, and adolescents selected by their teachers and peers. Twenty-seven teachers and 395 adolescents from public high schools completed mentalizing abilities, social status, behavioral, and peer buddy nomination measures. Findings suggest that social status and preference play a significant role in the selection of peer buddies by both teachers and classmates. Furthermore, more advanced Theory of Mind (ToM) abilities and the engagement in prosocial behaviors differentiated peers selected as buddies from other classmates. When compared with nonparticipating students, adolescents who expressed willingness to participate were more often girls, and were more prosocial. Agreement between teacher and peer nominations of best peer was moderate.